Favorable safety profile of NOAC therapy in patients after tricuspid transcatheter edge-to-edge repair - Hörbrand, Isabel; Volz, Martin J.; Gruber, Martin; Geis, Nicolas; Schlegel, Philipp; Frey, Norbert; Konstandin, Mathias (Clinical research in cardiology, 2025)
Background: Transcatheter edge-to-edge repair for severe tricuspid regurgitation (TR) is a new treatment option (t-TEER). Data on optimal antithrombotic therapy after t-TEER in patients with an indication for anticoagulation are scarce and evidence-based guideline recommendations are lacking. We sought to investigate efficacy and safety of novel oral anticoagulation (NOAC) and vitamin-K-antagonists (VKA) in patients undergoing t-TEER. Methods: Among 78 consecutive patients with t-TEER of severe TR, 69 patients were identified with concomitant indication for oral anticoagulation. Outcomes of these patients treated with NOAC or VKA were compared over a median follow-up period of 327 (177–460) days. Results: Despite elevated thromboembolic and bleeding risk scores (CHA2DS2-VASc 4.2 ± 1.1, HEMORR2HAGES 3.0 ± 1.0 and HAS-BLED 2.1 ± 0.8), only one major bleeding incidence occurred under NOAC therapy. The risk for overall (NOAC 8% vs. VKA group 26%, p = 0.044) and major bleeding events (NOAC 2% vs. VKA 21%, p = 0.010) was significantly lower in the NOAC compared to the VKA group. No significant difference was found between NOAC and VKA treatment in terms of mortality (NOAC 18% vs. VKA 16%, p = 0.865) or the combined endpoint of death, heart failure hospitalization, stroke, embolism, thrombosis, myocardial infarction, and severe bleeding (NOAC 48% vs. VKA 42%, p = 0.801). A comparison between apixaban (n = 27) and rivaroxaban (n = 16) treated patients revealed no significant differences between NOAC substances (all bleeding events apixaban 7% vs. rivaroxaban 13%, p = 0.638). Conclusion: Results of this study indicate that NOACs may offer a favorable risk–benefit profile for patients with concomitant indication for anticoagulation therapy following t-TEER.
Zuerst veröffentlicht: 19. August 2024
Gesehen am 04.11.2024